Ngalap Barokah Minuman Bekas Kiai Kajian Living Hadis Teori Sosial Emile Durkheim: Studi Kasus Pondok Pesantren An-Nur Komplek Nurul Huda Bantul Yogyakarta - M. Amirur Rahman (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2022)
This research was conducted at Pesantren An-Nur complex Nurul Huda Bantul Yogyakarta about the phenomenon of ngalap barokah from former kiai drinks. Based on the analysis carried out by the author that the hadiths related to ngalap barokah are quite widely found in Kutub at-Tis’ah, meaning that indirectly the santri an-Nur Nurul Huda has practised the guidance of the teachings of the prophet Muhammad SAW, through the practice of ngalap barokah drinks used Kiai, which is then referred to as living hadith. Emile Durkheim's sacred social theory of the practice of ngalap barokah drink used Kiai, this is at least some point that is considered sacred. firstly, humans, in this case, are the figure of a Kiai, secondly objects such as glasses, plates or trays used to drink Kiai, thirdly water, namely drinking water used by Kiai, and fourth places, namely the place used by the Kiai when sitting all these objects are considered sacred by students as a manifestation of sacred theory in the life of pesantren.